All Days 2015
DOI: 10.2118/175278-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steam-Foam Technology as an Option to Improve Steam Drive Efficiency

Abstract: The steam-foam process is an Enhanced Oil Recovery (EOR) method which aims to improve the performance of a traditional steam drive by using a foaming surfactant. A Canadian thermal project under development in NW Alberta, which will use steam drive to recover extra heavy oil from the Bluesky Reservoir, is a good candidate for the application of steam-foam. A pilot test is planned to evaluate the benefits of the steam-foam process in this reservoir.The steam-foam process is based on the use of a surfactant whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Foam-assisted steam flooding is an effective technology to improve the sweep efficiency of steam flooding by inhibiting the steam channeling and gravity override, thus increasing the oil recovery of steam flooding. The high-temperature foam agent can not only inhibit the steam overriding but also reduce the steam mobility. Besides, the foam also has the selective blocking characteristics, which can block the big pores rather than the small pores and block the water layers rather than the oil layers. , It is indicated that the foam is an ideal high-temperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. , The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta . Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. , …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Foam-assisted steam flooding is an effective technology to improve the sweep efficiency of steam flooding by inhibiting the steam channeling and gravity override, thus increasing the oil recovery of steam flooding. The high-temperature foam agent can not only inhibit the steam overriding but also reduce the steam mobility. Besides, the foam also has the selective blocking characteristics, which can block the big pores rather than the small pores and block the water layers rather than the oil layers. , It is indicated that the foam is an ideal high-temperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. , The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta . Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. , …”
Section: Introductionmentioning
confidence: 83%
“…6,7 The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta. 8 Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. 9,10 It is well-known that the foam thermal stability is the key problem in steam flooding to improve the sweep efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…communication and/or channeling in a layered formation with poor vertical communication between sand members. In order to minimize drawbacks of steamflooding, steam-foam flooding, the combination between surfactant and steamflooding, was developed [12]. Surfactant can reduce surface tension of liquid and then reduces the work needed to create foam.…”
Section: Surface Tension Diagram Of Oil Droplet and Surfactant Solutionmentioning
confidence: 99%